Analysis of bioeconomical and effectiveness of capture tuna fishery in coastal area of Sendang Biru, Malang, East Java Province - Fanani, M Zainal; Jamil, Khairul (Universitas Sam Ratulangi, 2013)
Tuna (Thunnus sp.) need to be managed well by maintaining balance between economic aspect (profits) and ecological aspect (sustainability of fish resources). To maintain balance these aspect to do with bioeconomical analysis. With these analysis be expected can be obtained maximum economic profits without any damage fish resources so that environmental conservation stay awake. In order to analyze the bioeconomical is needed to estimate the stock assessment. The first step is standardization of fishing gear, this need to be done because each of fishing gear not only catch the target fish but also catch the non target fish (multi gear multi spesies). Of the research be obtained standard gear for tuna fishery in Sendang Biru water are trolling line, with maximum value between payang, hand line and gillnet. Status of tuna fishery from biological aspect in Sendang Biru water by Schaefer model in general medium fishing condition. Whereas status of tuna fishery from economic aspect by Schaefer model in over exploited. Of the research by multi criteria decision making (MCDM) analysis with simple multi attribute rating technique (SMART) and visual interactive sensitivity analysis (VISA) obtainable that the main priority in election of tuna fishing gear evectively and efficient are trolling line, paying, hand line and gillnet© Perikanan tuna perlu dikelola dengan baik dengan cara menjaga keseimbangan antara aspek ekonomi (keuntungan) dan aspek ekologi (kelestarian sumberdaya ikan). Untuk menjaga keseimbangan aspek-aspek tersebut, dapat dilakukan dengan analisis bioekonomi. Dengan analisis ini diharapkan dapat diperoleh keuntungan ekonomi yang maksimum tanpa disertai kerusakan sumberdaya ikan sehingga konservasi lingkungan tetap terjaga. Dalam rangka menganalisa bioekonomi perlu dilakukan pendugaan stok ikan (‘stock assessment’). Langkah awal adalah standarisasi alat tangkap, hal ini perlu dilakukan karena setiap alat tangkap tidak hanya menangkap ikan target tapi juga menangkap ikan non target (‘multi gear multi spesies’). Dari hasil penelitian didapat alat tangkap standar untuk perikanan tuna di perairan Sendang Biru adalah pancing tonda dengan nilai porsi terbesar diantara alat tangkap payang, pancing tangan dan ‘gillnet’. Status perikanan tuna dari aspek biologi di perairan Sendang Biru menurut model Schaefer secara umum dalam kondisi ‘medium fishing’. Sedangkan status perikanan tuna secara ekonomi menurut model Schaefer dalam kondisi ‘over exploited’. Dari hasil analisis multi ‘criteria decision making’ (MCDM) dengan teknik ‘simple multi attribute rating technique’ (SMART) dan teknik ‘visual interactive sensitivity analysis’ (VISA) diperoleh bahwa prioritas yang utama dalam pemilihan alat tangkap tuna secara efektif dan efisien adalah pancing tonda, payang, pancing tangan dan gillnet©